Urban Ethnobotany in Argentina: Theoretical advances and methodological strategies - Hurrell, Julio Alberto (2014)
Urban Ethnobotany is a discipline of relatively recent development, allowing new questions and interesting challenges from both theoretical and methodological point of view. This has become evident from the development of a research line in the metropolitan area Buenos Aires-La Plata, the largest in extension and population of Argentina. This research was carried out in the Laboratorio de Etnobotánica y Botánica Aplicada (LEBA), Facultad de Ciencias Naturales y Museo, Universidad Nacional de La Plata, Argentina. In this frame, the ongoing investigations constitute an example of feedback between theory and practice in ethnobotanical studies. How the botanical knowledge is composed in urban pluricultural contexts? Is it possible to find traditional botanical knowledge in these contexts? How is the local botanical knowledge transmitted? How is its dynamic? Assuming the premise that knowledge guides the actions, then how botanical knowledge guides the selection and utilization strategies of plants and its products in urban areas? The aim of this contribution is try to answer these, and other relevant questions. Some basic principles about Ecology, Biocultural Ecology, and Ethnobotany as different levels of approximation within a unified field were discussed. Later, advances in the theoretical field of urban ethnobotany were considered, as reflection product on complexity of the obtained results. These advances were translated into methodological strategies based on different criteria to evaluate the urban botanical knowledge underlying the circulation of plant products (exclusivity and visibility of these products, re-signification of its uses in contexts of change). Finally, a reflexive discussion on complexity of theoretical and methodological contexts allows us to rethink the developments in Urban Ethnobotany, and Ethnobotany in general.